The Effect Of Liquid Organic Fertilizer (Lof) From Rice Washing Water and Coconut Water Using Em4 On The Growth Of Chorella sp. At Laboratory Scale - Lutur, Elen Marta; Ismail, Irwan; Irsan, Irsan; Rumakabis, Mega Utami (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2023)
Chlorella sp. has significantly higher nutritional content compared to artificial feed. To obtain Chlorella sp. as a natural feed, it was necessary to cultivate pure phytoplankton to meet the availability of crude feed in sufficient quantities. In conducting the cultivation, there was a need for liquid organic fertilizer (LOF) that could be easily obtained and was available in nature, which was liquid organic fertilizer made from a mixture of rice washing water and coconut water fermented using EM4. This research aimed to determine the density of Chlorella sp. using liquid organic fertilizer from rice washing water, and coconut water fermented using EM4 and the effect of the best fertilizer dosage on the growth of Chlorella sp. This research used a Completely Randomized Design (CRD) consisting of 4 treatments with four replications. The highest average cell density of Chlorella sp. throughout the research was obtained in treatment C (15 ml dosage), followed by treatment B (10 ml dosage), treatment D (20 ml dosage), and the lowest in treatment A (control). The application of liquid organic fertilizer from rice washing water and coconut water significantly affected the density of Chlorella sp. (p <0.05). The highest density was recorded on day 6 in treatment C with a dosage of rice washing water and coconut water of 15 ml, with a population density of 12,466.25 x 104 cells/ml.